Effects of selected herbal extracts on growth, disease resistance and immune response in Asian seabass, Lates calcarifer (Bloch, 1790) - Abdul Razak, Rashidah (2018)
Asian seabass, Lates calcarifer is among the main marine fish species cultured in Malaysia with the highest production. Nevertheless, disease outbreaks during culture periods have become a major constraint that contributes to severe economic losses. The frequent use of antibiotics for disease treatment has caused a negative impact with the development of resistant bacterial strains. Thus, the use of herbal treatments is now receiving greater attention as an alternative to overcome disease problems. As herbal medicine is effective in healing and curing human diseases it is also being applied as chemotherapeutics and feed additives in fish. Therefore, the general objective of this study was to determine the effect of herbal supplementation on the growth performance, immune response and disease resistance in Asian seabass. Extracts of Clinacanthus nutans, Syzygium polyanthum, Vitex negundo, Polygonum chinense, Alpinia conchigera, Premna feotida, Brucea javanica and Pimenta dioica were screened for their antimicrobial activities against the common marine fish pathogens, Vibrio harveyi, Vibrio parahaemolyticus, Vibrio alginolyticus and Aeromonas hydrophila using disk diffusion method. The results showed that the methanolic extracts of P. chinense, P. dioica and P. feotida, and aqueous extracts of S. polyanthum and P. dioica have moderate to strong antimicrobial activities against all tested pathogens at concentration of 300 mg/mL. These five crude extracts were further fractionated using methanol, dichloromethane and ethyl acetate whereby ethyl acetate fractions gave moderate, strong to very strong antimicrobial activities against all tested bacteria except for P. foetida extract against V. parahaemolyticus. Brine shrimp cytotoxicity study on the potential five crude extracts showed that only the methanolic extract of P. foetida and P. chinense have low toxicity while the others were moderately toxic. Therefore, extract of P. foetida (PFA) and P. chinense (PCE) were chosen for feed supplementation at concentrations of 2, 5 and 10 g/kg for 60 days, followed by challenged with V. harveyi for 14 days to investigate their potential as growth and disease resistance promoters in Asian seabass. The results showed that PCE at 5 g/kg (PCE-5) diet was the best fish growth promoter with 47.24 g/fish of body weight gain, 35.8 of feed efficiency, 1.14 specific growth rate and 98.8% survival. Fish fed with PCE-5 diet have also obtained significantly higher (p< 0.05) albumin, albumin: globulin ratio, phagocytic activity and serum total immunoglobulin compared with other diets on day 60. After two weeks of challenging study, all treatment diets showed significantly (p < 0.05) higher survival than the control. Fish fed with PCE-10 diet had the highest survival (90%), followed by PCE-5 and PCE-2 diets with 86.7% survival respectively. PCE-10 diet supplementation also showed significantly (p < 0.05) increases in some of the haemato-biochemical parameters, lysozyme and respiratory burst activities, and total immunoglobulin compared to the control. The histological study also revealed that fish fed with both plant extracts showed milder lesions compared to the control upon exposure to V. harveyi. Therefore, this study revealed that P. chinense supplementation in fish diet has a beneficial effect on the growth, survival, biochemical, immunological and disease resistance in Asian seabass.